Determinantes de la evolución del número de casos y muertes por COVID-19 en el Perú: movilidad, geografía y desarrollo económico - Seminario (†), Bruno (2022)
This research seeks to contribute to the literature on the determinants of the evolution of the number of cases and deaths from COVID-19 in Peru; specifically, the role of mobility of people —understood as displacement—, geography, and economic development. To do this, we use random-effects Poisson regressions and data from four groups of variables at the district level: (1) COVID-19, (2) mobility of people, (3) geographic variables, and (4) socioeconomic variables. The main results indicate that the mobility of people has a negative relationship with the probability of accumulating cases and deaths of COVID-19 until the ninth week of the pandemic, but it has a positive relationship from the eleventh week. We also find that socioeconomic variables such as GDP per capita and life expectancy have positive associations with the probability of accumulating COVID-19 cases and deaths, while geographic variables such as height and slope of the territory have negative associations. The results also indicate that the role of geographic and socioeconomic variables depends on the inclusion of Lima in the empirical analysis.